Iowa Birdline update, January 20, 1992 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1992)
Email of Iowa Birdline updates for January 20, 1992. The highlights for the update include sightings of several species of gulls, an adult Red-shouldered Hawk, Northern Saw-whet Owl and a Northern Shrike. Also included are handwritten notes with sightings of a male White-winged Crossbill and after being missing for over a week following the bitter cold, the Pine Warbler was back at the feeder in Pleasantville. Epson - sheet feed/flatbed